Sejarah Pendidikan Pesantren: Studi Pesantren sebagai Pembentuk Tradisi Islam Indonesia - Atin Hasanah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2022)
This paper will reveal the role of pesantren in shaping traditions in Indonesia. it has a distinctive pattern, which is the result of creativity in translating the heritage of two traditions at once, the West and the Middle East. The focus of the problem will be directed at Islamic boarding schools and Kyai. The formulations discussed are First, what are the roots of Islamic boarding schools in Indonesia, which make them cultural brokers? Second, how can pesantren become an established educational institution in the contestation of education in Indonesia in this modern era? Third, what is the form of the Islamic boarding school cultural broker in responding to the phenomenon of modernity in Indonesia? The approach used in discussing the formulation of the problem above is Postcolonial using the concept of Edward Said. From Said's approach and theoretical concept, the formulation of the problem above can be concluded first, the scientific root of pesantren is Islam during the Walisongo period. Second, Islamic boarding school education has become stable and established due to the emergence of the nation-state century. Third, there are two forms of cultural brokers from pesantren, namely pesantren and Kyai figures.